Utilizing murine dendritic cell line DC2.4 to evaluate the immunogenicity of subunit vaccines in vitro - Lu, Lantian; Kong, Wei Yang; Zhang, Jiahui; Firdaus, Farrhana; Wells, James W.; Stephenson, Rachel J.; Toth, Istvan; Skwarczynski, Mariusz; Cruz, Jazmina L. Gonzalez (Frontiers in Immunology, 2024)
Subunit vaccines hold substantial promise in controlling infectious diseases, due to their superior safety profile, specific immunogenicity, simplified manufacturing processes, and well-defined chemical compositions. One of the most important end-targets of vaccines is a subset of lymphocytes originating from the thymus, known as T cells, which possess the ability to mount an antigen-specific immune response. Furthermore, vaccines confer long-term immunity through the generation of memory T cell pools. Dendritic cells are essential for the activation of T cells and the induction of adaptive immunity, making them key for the in vitro evaluation of vaccine efficacy. Upon internalization by dendritic cells, vaccine-bearing antigens are processed, and suitable fragments are presented to T cells by major histocompatibility complex (MHC) molecules. In addition, DCs can secrete various cytokines to crosstalk with T cells to coordinate subsequent immune responses. Here, we generated an in vitro model using the immortalized murine dendritic cell line, DC2.4, to recapitulate the process of antigen uptake and DC maturation, measured as the elevation of CD40, MHC-II, CD80 and CD86 on the cell surface. The levels of key DC cytokines, tumor necrosis alpha (TNF-α) and interleukin-10 (IL-10) were measured to better define DC activation. This information served as a cost-effective and rapid proxy for assessing the antigen presentation efficacy of various vaccine formulations, demonstrating a strong correlation with previously published in vivo study outcomes. Hence, our assay enables the selection of the lead vaccine candidates based on DC activation capacity prior to in vivo animal studies.